2007
DOI: 10.1016/j.nuclcard.2007.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of a novel wide beam reconstruction method for shortening scan time of Tc-99m cardiac SPECT perfusion studies

Abstract: Our study results suggest that cardiac single photon emission computed tomography perfusion studies may be performed with the WBR algorithm using half of the scan time without compromising qualitative or quantitative imaging results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(79 citation statements)
references
References 6 publications
2
77
0
Order By: Relevance
“…44,45 The use of time imaging software which incorporates iterative image reconstruction with resolution recovery thereby improving count statistics can decrease imaging time or decrease injected activity. 46 Stress protocol changes such as performing more ETTs, 47 developing a provisional isotope injection protocol, 38 and stress-first imaging 10 will all decrease radiation exposure to the patient by not giving it in the first place. Perhaps the greatest saving of radiation exposure and resources would be the elimination of any diagnostic testing for most of the very low-and low-risk patients (''less is more'').…”
Section: 6mentioning
confidence: 99%
“…44,45 The use of time imaging software which incorporates iterative image reconstruction with resolution recovery thereby improving count statistics can decrease imaging time or decrease injected activity. 46 Stress protocol changes such as performing more ETTs, 47 developing a provisional isotope injection protocol, 38 and stress-first imaging 10 will all decrease radiation exposure to the patient by not giving it in the first place. Perhaps the greatest saving of radiation exposure and resources would be the elimination of any diagnostic testing for most of the very low-and low-risk patients (''less is more'').…”
Section: 6mentioning
confidence: 99%
“…8 In addition to the nSPEED software developed by Digirad, there are other 3D reconstruction software packages that also claim the capability of allowing shortened scanning time while maintaining or improving image quality and quantitation. These techniques include the Wide-Beam Reconstruction (WBR) from Ultra-SPECT, 9,10 the Flash-3D from Siemens, Astonish from Philips, and Evolution from GE. The physics principle of all the 3D reconstruction packages is the same, i.e., to model the 3D depth-dependent detector spatial response and to suppress the noise to achieve the best compromise of resolution/contrast improvement and noise reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Borges-Neto et al (16) tested WBR and FBP and found no statistically significant differences in summed stress scores (SSS), summed rest scores (SRS), and summed difference scores (SDS) but did note a statistically significant difference for the EF, citing improved resolution as the probable cause. Additionally, Zoccarato et al (17) Although the acquisition times for WBR are generally described to be one half those for FBP, DePuey et al (19) examined the feasibility of reducing the acquisition times further, to one fourth those for FBP.…”
Section: Spect Mpi and Gated Spect Mpimentioning
confidence: 99%